Generating retinoic acid gradients by local degradation during craniofacial development: One cell's cue is another cell's poison. Issue 2 (25th January 2018) - Dubey, Aditi; Rose, Rebecca E.; Jones, Drew R.; Saint‐Jeannet, Jean‐Pierre
Summary: Retinoic acid (RA) is a vital morphogen for early patterning and organogenesis in the developing embryo. RA is a diffusible, lipophilic molecule that signals via nuclear RA receptor heterodimeric units that regulate gene expression by interacting with RA response elements in promoters of a significant number of genes. For precise RA signaling, a robust gradient of the morphogen is required. The developing embryo contains regions that produce RA, and specific intracellular concentrations of RA are created through local degradation mediated by Cyp26 enzymes. In order to elucidate the mechanisms by which RA executes precise developmental programs, the kinetics of RA metabolism must be clearly understood. Recent advances in techniques for endogenous RA detection and quantification have paved the way for mechanistic studies to shed light on downstream gene expression regulation coordinated by RA. It is increasingly coming to light that RA signaling operates not only at precise concentrations but also employs mechanisms of degradation and feedback inhibition to self‐regulate its levels. A global gradient of RA throughout the embryo is often found concurrently with several local gradients, created by juxtaposed domains of RA synthesis and degradation. The existence of such local gradients has been found especially critical for the proper development of craniofacial structures that arise from the neural crest and the cranial placode populations. In this review, we summarize the current understanding of how local gradients of RA are established in the embryo and their impact on craniofacial development.